Miniaturized antibodies for imaging membrane type‐1 matrix metalloproteinase in cancers. Issue 4 (17th February 2013) - Kondo, Naoya; Temma, Takashi; Shimizu, Yoichi; Watanabe, Hiroyuki; Higano, Keiichi; Takagi, Yoko; Ono, Masahiro; Saji, Hideo
<x xml:space="preserve">Abstract</x> Since membrane type‐1 matrix metalloproteinase (MT1‐MMP) plays pivotal roles in tumor progression and metastasis and holds great promise as an early biomarker for malignant tumors, a method of evaluating MT1‐MMP expression levels would be valuable for molecular biological and clinical studies. Although we have previously developed a 99mTc‐labeled anti‐MT1‐MMP monoclonal IgG (99mTc‐MT1‐mAb) as an MT1‐MMP imaging probe by nuclear medical techniques for this purpose, slow pharmacokinetics were a problem due to its large molecular size. Thus, in this study, our aim was to develop miniaturized antibodies, a single chain antibody fragment (MT1‐scFv) and a dimer of two molecules of scFv (MT1‐diabody), as the basic structures of MT1‐MMP imaging probes followed by in vitro and in vivo evaluation with an 111In radiolabel. Phage display screening successfully provided MT1‐scFv and MT1‐diabody, which had sufficiently high affinity for MT1‐MMP (KD = 29.8 and 17.1 nM). Both 111In labeled miniaturized antibodies showed higher uptake in MT1‐MMP expressing HT1080 cells than in non‐expressing MCF7 cells. An in vivo biodistribution study showed rapid pharmacokinetics for both probes, which exhibited >20‐fold higher tumor to blood radioactivity ratios (T/B ratio), an index for in vivo imaging, than 99mTc‐MT1‐mAb 6 h post‐administration, and significantly higher tumor accumulation in HT1080 than MCF7 cells. SPECT images showed heterogeneous distribution and ex vivo autoradiographic analysis revealed that the radioactivity distribution profiles in tumors corresponded to MT1‐MMP‐positive areas. These findings suggest that the newly developed miniaturized antibodies are promising probes for detection of MT1‐MMP in cancer cells.